Problematic substance use: an assessment of workplace implications in midwifery. (19th September 2021) - Pezaro, S; Maher, K; Bailey, E; Pearce, G
Abstract: Background: Problematic substance use (PSU) poses occupational, personal and professional risks. As an occupational group, midwives have been under-represented in research on PSU. Aims: The aim of this study was to assess self-reported occurrences of PSU, help-seeking behaviours and barriers, and perceptions of impairment in UK-based midwives. Methods: Self-selecting registered midwives were anonymously surveyed using the Tobacco, Alcohol, Prescription Medications, and Substance Use/Misuse (TAPS) tool, the Perceptions of Nursing Impairment Inventory (PNII) and open-ended/closed questions. Quantitative data were used to explore PSU, help-seeking and attitudes to impairment. Qualitative responses were used to provide richer understandings. Results: From 623 completed surveys, 28% ( n = 176) self-reported PSU in response to work-related stress and anxiety, bullying, traumatic clinical incidents and maintenance of overall functioning. PSU was related to alcohol and a range of restricted drugs. While 11% of those affected indicated they had sought help, 27% felt they should seek help but did not. Reported barriers to help-seeking included fear of repercussions, shame, stigma, practicalities and a perceived lack of support either available or required. Perceptions of impairment were predominantly compassionate with a minority of stigmatizing attitudes displayed. Conclusions: Overall, 10% of the sample reported they had attended work under the influence of alcohol, and 6% under the influence of drugs other than tobacco or those as prescribed to them. Furthermore, 37% indicated concern about a colleague's substance use. As stigmatizing attitudes and punitive actions can dissuade help-seeking, changed perceptions and policies which favour alternatives to discipline are suggested to reduce the risk overall.